STRATEGI PENANGANAN PANDEMI COVID-19 MELALUI OPTIMALISASI TEKNOLOGI INFORMASI DI KABUPATEN GARUT - Pujo Laksono; Ryan Akbar Maulana; Ratih Khairunnisa (Jurnal Pemerintahan Dan Keamanan Publik (JP dan KP), 2021)
Every day the number of cases caused by the Covid-19 pandemic continues to grow. The Covid-19 pandemic has forced the government to formulate policies to reduce the number of its spread. With various policies made by the government, community activities and information dissemination are limited. This paper aims to find out strategies for handling the Covid-19 pandemic through optimizing information technology. We need to know that the Covid-19 pandemic continues to increase every day, which requires people to limit their environment and implement social distancing. Information Technology has the goal of solving a problem, opening up creativity, increasing effectiveness and efficiency in doing work. Information technology innovations continue to be developed as the number of Covid-19 patients increases. Many countries have used information technology to find out information on the development of Covid-19 over long distances by using internet media in preventing Covid-19. The internet also helps Covid-19 patients with doctors, and helps make it easier for people to complete work. Garut Regency, West Java is one of the districts that experienced a significant increase in the number of cases. The local government has also pursued a strategy to deal with Covid-19 by optimizing information technology through the internet. From the data found, it can be concluded that information technology can help in handling Covid-19, especially in Garut Regency. Keywords: Information Technology, Covid-19, Garut Regency